Impact of Government Intervention on Inflation Control - Ashraf, Mohammad A.; Rodriguez, Gabriel (Asian Journal of Applied Economics, 2013)
บทคัดย่อ บทความนี้ ตรวจสอบผลกระทบการควบคุมเงินเฟ้อจากการแทรกแซงของรัฐ โดยใช้ เทคนิคพยากรณ์เพื่อคำนวณค่า fractional parameter และให้มี additive inliers ที่ สะท้อนถึงนโยบายแทรกแซง การวิเคราะห์ พิจารณากรณีใีห้มีแผนกระตุ้น ระยะสั้นที่ สำคัญ ผลการศึกษาชี้ว่า่ การแทรกแซงของรัฐจะเป็นผลต่อการควบคุมเงินเฟ้อเพียง ในระยะชั่วคราว การศึกษานี้จึงเสนอทางเลือกในการควบคุมเงินเฟ้อ โดยน่าจะพิจารณาใช้นโยบายเศรษฐกิจที่มีความเหมาะสมกับสถานการณ์เวลาที่สามารถจัดการ ปัญหาเงินเฟ้อ และขณะเดียวกันสามารถควบคุมเงินเฟ้อได้ในระยะยาว คำสำคัญ : นโยบายการเงิน, การควบคุมเงินเฟ้อ Abstract This paper detects the effects of government intervention to control inflation. The long memory fractional parameter was estimated using simulation technique in the presence of additive inliers, which serve as a proxy of government intervention. The data generating process considers the case where there are shock plans, i.e. inliers that are short-lived but important in magnitude. The results show that the level to which inflation falls after the intervention has no impact on the estimate of the fractional parameter and on the persistence of the inflation process. That means any abrupt intervention would have only temporary effect on lowering the inflation rates and the series remain stationary. This implies the need for alternative measures of monetary policy. This paper recommends pursuing the time-consistency economic policy, which provides an explanation in order to combat inflation and to sustain the result for the longer period. Keywords : additive inliers, fractional parameter, Monte-Carlo simulation, inflation control